Orthopaedic examination techniques : a practical guide - 4 0 16; 1962-;1965- Ali, Fazal,;Harris, Nick; 5 Ohio Library and Information Network (Cambridge : Cambridge University Press, 2022)
Orthopaedic Examination Techniques comprehensively covers the basic examination skills and key special tests needed to evaluate the adult and paediatric musculoskeletal system. Chapters are presented in a clear and logical way to allow readers to understand then master the techniques of orthopaedic clinical examination. Written by a diverse group of chapter authors with extensive experience in teaching clinical examination and who use a uniform system that is taught on national courses, every aspect of musculoskeletal examination is covered in the adult and paediatric patient. Numerous illustrations and new clinical photographs help readers to visualise and understand the key techniques, and five new chapters at the end of the book demonstrate the value of clinical examination through more than 80 clinical case examples. Easy-to-follow throughout, this book is invaluable reading for trainee orthopaedic surgeons, especially those preparing for the FRCS (Tr&Orth) postgraduate examination, practising orthopaedic surgeons, medical students, physiotherapists, and rheumatologists
Title from publisher's bibliographic system (viewed on 07 Apr 2022)
Keywords: 2 -- 0; 6; Examination -- Musculoskeletal system -- 20; 20; Electronic books -- 2